The Indian Ocean - Taylor, Leighton; Wu, Norbert (Woodbridge, Conn. : Blackbirch Press, 1998)
Text and photographs present information about the Indian Ocean, its location, physical environment, animal life, islands, and mysteries.
Includes index.
Includes glossary.
Includes bibliography.
4-8
AR Accelerated Reader
Keywords: Indian Ocean -- Juvenile literature